Identifying knowledge gaps in understanding the effects of selective serotonin reuptake inhibitors (SSRIs) on fish behaviour - Ferreira, Carla S. S. (2023)
Selective serotonin reuptake inhibitors (SSRIs) are a class of antidepressants increasingly prescribed to treat patients with clinical depression. As a result of the significant negative impact of the COVID-19 pandemic on the population's mental health, its consumption is expected to increase even more. The high consumption of these substances leads to their environmental dissemination, with evidence of their ability to compromise molecular, biochemical, physiological, and behavioural endpoints in non-target organisms. This study aimed to provide a critical review of the current knowledge regarding the effects of SSRI antidepressants on fish ecologically relevant behaviours and personality-dependent traits. A literature review shows limited data concerning the impact of fish personality on their responses to contaminants and how such responses could be influenced by SSRIs. This lack of information may be attributable to a lack of widely adopted standardized protocols for evaluating behavioural responses in fish. The existing studies examining the effects of SSRIs across various biological levels overlook the intra-specific variations in behaviour and physiology associated with different personality patterns or coping styles. Consequently, some effects may remain undetected, such as variations in coping styles and the capacity to handle environmental stressors. This oversight could potentially result in long-term effects with ecological implications. Data support the need for more studies to understand the impact of SSRIs on personality-dependent traits and how they may impair fitness-related behaviours. Given the considerable cross-species similarity in the personality dimensions, the collected data may allow new insights into the correlation between personality and animal fitness.